2015
DOI: 10.1007/s10802-015-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in Children with Conduct Problems and Callous-Unemotional Traits: Social Information Processing and Response to Peer Provocation

Abstract: Callous/unemotional traits (CU) moderate children's conduct problems (CP) in numerous domains, including social functioning. The present study examined whether CU traits also moderate the aggressiveness of children's social information processing (SIP) and responses to varying intensities of peer provocation. Sixty elementary school-age children (46 males) were grouped into those without CP or CU (controls, n = 32), those with CP but not CU (CP-only; n = 14), and those with both CP and CU (CPCU, n = 14). Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 48 publications
(64 reference statements)
0
22
1
Order By: Relevance
“…As both children with CP-CU as well as children with CP-only show increased levels of reactive aggression [33] our findings of a tendency for a higher hostile attribution bias in both of these groups fit the results of a meta-analysis, showing that reactive aggression is associated with higher levels of the hostile attribution bias [14]. Nonetheless, our findings contradict the previous finding of a stronger hostile attribution bias in CP-only compared to CP-CU children [31], the findings of a higher hostile attribution bias in CP-CU compared to CP-only children [32] and the findings of no group differences at all [15]. Our study overcame several shortcomings of these previous studies.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…As both children with CP-CU as well as children with CP-only show increased levels of reactive aggression [33] our findings of a tendency for a higher hostile attribution bias in both of these groups fit the results of a meta-analysis, showing that reactive aggression is associated with higher levels of the hostile attribution bias [14]. Nonetheless, our findings contradict the previous finding of a stronger hostile attribution bias in CP-only compared to CP-CU children [31], the findings of a higher hostile attribution bias in CP-CU compared to CP-only children [32] and the findings of no group differences at all [15]. Our study overcame several shortcomings of these previous studies.…”
Section: Discussioncontrasting
confidence: 53%
“…However, studies, which directly investigated the hostile attribution bias in children with CP and CU-traits, produced inconsistent results. Frick et al [31] reported an increased hostile attribution bias in boys with CP-only compared to all other groups, Cima et al [32] observed an increased hostile attribution bias in CP-CU boys compared to CP-only boys, and Helseth et al did not find any group differences [15]. As Cima et al [32] only investigated boys, Frick [31] only observed group differences in the male portion of their study sample and Helseth et al [15] did not observe any group differences in their mixed gender sample, gender might be a potential confounding factor and explain the discrepancies between these results.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…We included these initial three fully unprovoked trials to examine participants responses prior and after the onset of provocation. Having trials in which participants have not yet received a noise blast from the opponent can provide an important baseline measure of aggression (e.g., Helseth, Waschbusch, King & Willoughby, ). On the remaining trials, some constraints were programmed to manipulate the number and levels of noise participants received in a randomized order.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that the increased attention to distress cues noted among CU youth experiencing anxiety represents a sensitivity to negative emotional cues in general, similar to the attentional biases towards negative-and threat-related cues (Mogg & Bradley, 2005;Reid et al, 2006), and bias towards interpreting ambiguous information negatively (Taghavi et al, 2000) documented among anxious children. While CU traits have not previously been associated with a hostile attribution bias (HAB; Dodge, Price, Bachorowski, & Newman, 1990;Frick et al, 2003a;Helseth, Waschbusch, King, & Willoughby, 2015), perhaps the combination of cognitive biases associated with anxiety and the callousness of CU traits yields the impulsive, aggressive reactivity documented in these youth (e.g., Fanti et al, 2013;Kahn et al, 2013).…”
Section: Aggressionmentioning
confidence: 99%